2014
DOI: 10.1111/1348-0421.12133
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of extracts from Morinda citrifolia leaves and chlorophyll catabolites, pheophorbide a and pyropheophorbide a, against hepatitis C virus

Abstract: The development of complementary and/or alternative drugs for treatment of hepatitis C virus (HCV) infection is still needed. Antiviral compounds in medicinal plants are potentially good targets to study. Morinda citrifolia is a common plant distributed widely in Indo-Pacific region; its fruits and leaves are food sources and are also used as a treatment in traditional medicine. In this study, using a HCV cell culture system, it was demonstrated that a methanol extract, its n-hexane, and ethyl acetate fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…We tested ethanol extracts of Indonesia plants for their anti-HCV activities and reported that Toona sureni leaves, Melicope latifolia leaves, Melanolepis multiglandulosa stem and Ficus fistulosa leaves possessed anti-HCV activities [10]. We also reported that extracts of Glycyrrhiza uralensis root and isolated compounds, such as glycycoumarin, glycerin, glycyrol, and liquiritigenin, and extracts of Morinda citrifolia leaves, an isolated compound, pheophorbide a, and its related compound, pyropheophorbide a, exhibited anti-HCV activities [11,12]. Likewise, silymarin, iridoid, epigallocatechin-3-gallate were reported to inhibit HCV infection at the entry step while diosgenin, luteolin, quercetin, 3-hydroxy caruilignan C, excoecariphenol D and apigenin at the post-entry step [13,14].…”
Section: Introductionmentioning
confidence: 94%
“…We tested ethanol extracts of Indonesia plants for their anti-HCV activities and reported that Toona sureni leaves, Melicope latifolia leaves, Melanolepis multiglandulosa stem and Ficus fistulosa leaves possessed anti-HCV activities [10]. We also reported that extracts of Glycyrrhiza uralensis root and isolated compounds, such as glycycoumarin, glycerin, glycyrol, and liquiritigenin, and extracts of Morinda citrifolia leaves, an isolated compound, pheophorbide a, and its related compound, pyropheophorbide a, exhibited anti-HCV activities [11,12]. Likewise, silymarin, iridoid, epigallocatechin-3-gallate were reported to inhibit HCV infection at the entry step while diosgenin, luteolin, quercetin, 3-hydroxy caruilignan C, excoecariphenol D and apigenin at the post-entry step [13,14].…”
Section: Introductionmentioning
confidence: 94%
“…In addition to inhibiting HCV entry, compounds also inhibit viral infection after entry. Ratnoglik et al found that pheophorbide A and pyropheophorbide, two active compounds isolated from Morinda citrifolia, inhibited HCV infection by interrupting viral RNA replication and viral protein production (63). Silybin B, a silymarin isolated from Silybum marianum, inhibited HCV infection in 2 ways (64).…”
Section: Bioactive Compounds In Tcms To Treat Hcvmentioning
confidence: 99%
“…A major catabolite of chlorophyll A, which was isolated from Morinda citrifolia and identified as pheophorbide A, was reported to possess anti-HCV activity with IC 50 value of 0.3 µg/ml. It was reported also that pyropheophorbide A is an anti-HCV compound with IC 50 value of 0.2 µg/ml [10]. Adianti et al suggested that glycycoumarin, glycerin, glycerol, and liquiritigenin isolated from Glycyrrhiza uralensis, as well as isoliquiritigenin, licochalcone A, and glabridin, would be good candidates for seed compounds to develop antivirals against HCV [11].…”
Section: Introductionmentioning
confidence: 99%